Report of the Committee To Study the Development of Sericulture Industry in the North-Eastern Region - Planning Commission (Planning Commission, 1988)
During Annual Plan 1987-88 discussions with the State Chief Ministers, the then Deputy Chairman, Planning Commission noted that the production of raw silk in the States of Arunachal Pradesh and Tripura was incredibly low even though adequate outlays had annually been provided for sericulture industry under their State’s Plans. When the data relating to the production of raw silk in the remaining States of north eastern region was perused, it was found that sericulture industry failed to register any steady progress in terms of production but also witnessed downswings even though considerable infrastructure had been created in the region over Five Year Plans.
Planning Commission Government of India
Planning Commission Government of India